A Flexible shaft-driven Remote and Torsionally Compliant Actuator (RTCA) for wearable robots. (May 2019) - Rodriguez-Cianca, D.; Rodriguez-Guerrero, C.; Verstraten, T.; Jimenez-Fabian, R.; Vanderborght, B.; Lefeber, D.
Abstract: This paper presents the conceptual development and validation tests of a novel actuation paradigm for wearable robots, the flexible shaft-driven Remote and Torsionally Compliant Actuator. The RTCA exploits both the torsional compliance and bending properties of a commercial flexible shaft to provide simultaneously the advantages of remote actuation systems: improved weight distribution and reduced inertia on the distal joints, together with the advantages of compliant systems. The flexible shaft can be modelled following the proposed methodology as a torsionally compliant element that can be bent, so that the RTCA's output transmitted torque can be estimated based on the flexible shaft's torsional deflection angle and spatial configuration, allowing accurate torque control at the distal joint following a remote actuation approach based only on position sensors. Torque control and transparency tests were used to validate the proposed torque estimation and control approach. Finally, we presented a realistic implementation approach of the RTCA concept into a test bench resembling a lower limb exoskeleton as a case study for wearable robots. Results confirmed the capabilities of the proposed approach and supported the envisioned advantages of this novel actuation paradigm, constituting a promising solution for future developments in this field.